Karya Cipta Lagu dan Musik dalam Bingkai Asas Perlindungan Hukum - Ongriwalu, Adolf Djatmiko; Yunanto, Yunanto (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of this research is to find out the form of legal protection for a work of copyrighted songs and music which is plagiarism and what sanctions are given to perpetrators of plagiarism for a copyrighted song. The research methodology used is juridical-normative - that is, by collecting material related to several facts by offering appropriate data interpretations. The goal is to create methodical descriptions, illustrations, and information about the problem the author is researching. The conclusion of this research is 1. Legal protection for copyright, especially plagiarism in copyright law, has specified criteria for violations and imposition of sanctions as well as the existence of severe criminal penalties for perpetrators of copyright infringement, 2. Looking at the philosophy of punishment, restorative justice strategies can be used to complete the punishment imposed on those who commit acts of plagiarism of song and musical works of art.